(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Review of Nasia Hadjigeorgiou, Protecting Human Rights and Building Peace in Post-Violence Societies (Human Rights Law in Perspective), Hart Publishing (London: Bloomsbury Academic, 2020). 248pp. £49 (ebook). ISBN 9781509923427.